1991
DOI: 10.2105/ajph.81.3.365
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of drug abuser treatment needs in Rhode Island.

Abstract: BACKGROUND. Rhode Island's Division of Substance Abuse asked us to assess the State's drug treatment needs and make recommendations regarding its treatment system for the next three years. METHODS. We used a statewide telephone drug use survey of 5,176 households supplemented by drug-related hospital discharges, Division of Drug Control statistics, and interviews with providers, state officials, and out-of-state experts. Drug abuse was measured with items from the Diagnostic Interview Schedule. Abusers were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…37 In this report, 3 groups were identified as likely to benefit from specialty treatment: drug users (drug abuse treatment), alcoholic persons with or without drug use who met the DSM-IV alcohol dependence or abuse criteria (alcohol abuse treatment), and those meeting DSM-IV criteria for PTSD with or without drug use (psychiatric treatment). Although our criteria for individuals potentially needing drug abuse treatment differ from others, 38 the inclusion of all current and recent drug users was judged optimal, given the long-term nature of drug use in this cohort.…”
Section: Comorbiditymentioning
confidence: 99%
“…37 In this report, 3 groups were identified as likely to benefit from specialty treatment: drug users (drug abuse treatment), alcoholic persons with or without drug use who met the DSM-IV alcohol dependence or abuse criteria (alcohol abuse treatment), and those meeting DSM-IV criteria for PTSD with or without drug use (psychiatric treatment). Although our criteria for individuals potentially needing drug abuse treatment differ from others, 38 the inclusion of all current and recent drug users was judged optimal, given the long-term nature of drug use in this cohort.…”
Section: Comorbiditymentioning
confidence: 99%
“…We identified only one such study in our review [57]. Unlike health services research, epidemiological or psychosocial research typically does not prioritize service system planning.…”
Section: Discussionmentioning
confidence: 99%
“…The cost estimate of eliminating unmet need could be more precise because it would reflect the characteristics of those who still needed treatment, rather than those who had obtained it. In an earlier effort, McAuliffe et al (1991) lacked this information and therefore had to assume that the mix of needed drug treatment services would be the same as Rhode Island's mix. The authors recognized that the assumption was unlikely to be entirely accurate.…”
Section: Discussionmentioning
confidence: 99%
“…The 2002 National Survey of Drug Use and Health (NSDUH) estimated that only 10.3% of the 22.8 million individuals with a substance use disorder had received treatment at a specialty substance abuse facility in the past year (SAMHSA, 2003a). Other national surveys, as well as studies of the treatment gap in Maryland, New Jersey, Rhode Island, and other states and communities, have also found that large percentages of individuals with substance abuse and dependence diagnoses have not obtained treatment (Johnson, Brems, & Fisher, 1996;Mammo, 1993;McAuliffe, Breer, Ahmadifar, & Spino, 1991;Petronis & Wish, 1996). To provide services to all of the people identified in these surveys as needing treatment, substance abuse treatment services would typically have to increase 5-10 times the current service levels.…”
mentioning
confidence: 99%
See 1 more Smart Citation